High-Technology Batch Production Systems: Woodwards Missing Type - Hull, Frank M.; Collins, Paul (Academy of Management Journal, 1987)
The article examines Woodward's typology for classifying technology that distinguished between batch, mass and continuous-process production systems. A discussion is presented about the impact of r...